Altered whole-brain connectivity in albinism - Welton, Thomas; Ather, Sarim; Proudlock, Frank A.; Gottlob, Irene; Dineen, Robert A. (Wiley, 2016)
Albinism is a group of congenital disorders of the melanin synthesis pathway. Multiple ocular, white matter and cortical abnormalities occur in albinism, including a greater decussation of nerve fibres at the optic chiasm, foveal hypoplasia and nystagmus. Despite this, visual perception is largely preserved. It was proposed that this may be attributable to reorganisation among cerebral networks, including an increased interhemispheric connectivity of the primary visual areas. A graph-theoretic model was applied to explore brain connectivity networks derived from resting-state functional and diffusion-tensor magnetic resonance imaging data in 23 people with albinism and 20 controls. They tested for group differences in connectivity between primary visual areas and in summary network organisation descriptors. Main findings were supplemented with analyses of control regions, brain volumes and white matter microstructure. Significant functional interhemispheric hyperconnectivity of the primary visual areas in the albinism group were found (P = 0.012). Tests of interhemispheric connectivity based on the diffusion-tensor data showed no significant group difference (P = 0.713). Second, it was found that a range of functional whole-brain network metrics were abnormal in people with albinism, including the clustering coefficient (P = 0.005), although this may have been driven partly by overall differences in connectivity, rather than reorganisation. Based on the results, it was suggested that changes occur in albinism at the whole-brain level, and not just within the visual processing pathways. It was proposed that their findings may reflect compensatory adaptations to increased chiasmic decussation, foveal hypoplasia and nystagmus.